System zarządzania środowiskowego EMAS jako narzędzie wdrażania strategii zrównoważonego rozwoju w przedsiębiorstwie - Łokuciejewska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The concept of sustainable development is an important issue for Polish enterprises. It mostly depends on local authorities whether the country’s economic development will take place at the expense of environmental degradation or not. Environmental management systems can be helpful and will be able to change the perspective of our country which entered the elitarian club of European Union Member States. This entails the need to adhere to the Western standards. Promoting pro-en-vironmental behavior is no longer amatter of fashion but an obligation sanctioned by international law. Poland must adapt to the current standards. It could be done best through the involvement of individuals who contribute the most to the economic growth. Observing the situation in Lower Silesia, the conception of sustainability development is rather unpopular among the enterprises. Generally in 2014 there were only 4 companies out of 43 in the whole country which implemented the EMAS system. The results of the leading European states — Germany and Spain, show the backwardness of our country in this regard. Acontentious issue is a perspective of slowing down Polish economic development through the strict EU standards established by the Directives, however, as the name suggests — sustainable development can provide a positive prognosis for our economy and a sustained increase in the following years.
Keywords: zrównoważony rozwój; zarządzanie; Dolny Śląsk